PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN CINCAU STATION TUNJUNGAN PLAZA SURABAYA - Johana, Esther; Ayu, Stephanie Astrid (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the effect of price and product quality on customer loyalty at Cincau Station Tunjungan Plaza Surabaya. This study is based on the rapid growth of the food and beverage industry in Indonesia, especially in East Java, as well as the increasing business competition that requires companies to maintain loyal customers for business continuity. Cincau Station, as one of the beverage brands that has been operating since 2005, must face challenges in maintaining customer loyalty amidst tight competition. Therefore, this study was conducted to determine the extent to which price and product quality affect customer loyalty. The population in this study were Cincau Station customers at the Tunjungan Plaza Surabaya branch, with a sample of 75 respondents taken using purposive sampling techniques. Data were collected through questionnaires and analyzed using statistical analysis using SPSS software version 26.0. The results of the study indicate that price and product quality have a significant effect on customer loyalty. Overall, the independent variables (price, and product quality) are able to explain 60% in predicting customer loyalty, while the remaining 40% is explained by other variables outside this study.